Morphological and functional convergence of visual projection neurons from diverse neurogenic origins in Drosophila - Rana Naja El-Danaf; Katarina Kapuralin; Raghuvanshi Rajesh; Félix Simon; Nizar Drou; Filipe Pinto-Teixeira; Mehmet Neset Özel; Claude Desplan (Nature Communications)
Abstract The Drosophila visual system is a powerful model to study the development of neural circuits. Lobula columnar neurons-LCNs are visual output neurons that encode visual features relevant to natural behavior. There are ~20 classes of LCNs forming non-overlapping synaptic optic glomeruli in the brain. To address their origin, we used single-cell mRNA sequencing to define the transcriptome of LCN subtypes and identified lines that are expressed throughout their development. We show that LCNs originate from stem cells in four distinct brain regions exhibiting different modes of neurogenesis, including the ventral and dorsal tips of the outer proliferation center, the ventral superficial inner proliferation center and the central brain. We show that this convergence of similar neurons illustrates the complexity of generating neuronal diversity, and likely reflects the evolutionary origin of each subtype that detects a specific visual feature and might influence behaviors specific to each species.